Pengembangan Perangkat Lunak Pengolahan Data Farmasi Pada Klinik Kesehatan - Agung Suryadi; Andi Yulianto (Universitas Duta Bangsa Surakarta, 2020)
Disruptive innovation makes it possible for various data management and delivery of information using more information technology. The development of information technology, which is fast and advanced, has a very influential role in various services. For the sake of creating complete services, all health service providers need a system in serving patients. One of the services that currently requires accuracy is the pharmacy department.Pharmacy is a vital part of the health sector. The problem that often arises in data management activities in the pharmaceutical sector is the need for time in fast drug transaction services. The obstacle when implementing it using conventional methods is that it takes a long time and requires more accuracy so that services are hampered.By applying information technology in managing pharmaceutical data, it is able to provide convenience in managing drug data and producing the required reports. The purpose of this research is to build a pharmaceutical data management software that is able to provide convenience in computerized pharmaceutical data management, so that data and information can be stored and managed effectively and efficiently. This research is expected to provide solutions to health services, especially in the field of pharmacy, to provide good service so as to improve the quality of service to patients.